TRANSLATION NORMS AND QUALITY CONTROL OF A TRANSLATION - Muhammadjonova Gullola Elmurod qizi; Jo’rayeva Shaxzoda Otabek qizi; Tillayeva Iroda To’lqin qizi (Journal of new century innovations, 2024)
Norms refers to behaviour and attitudes which are considered normal, while values are those things that people consider important to them. Norms are believed to specify what is tolerated and allowed in a certain behavioural dimension, ensure the retention of social order and are acquired by each person during his or her socialisation. This is why translation involves at least two sets of norm-systems when it concerns at least two languages.